SARS-CoV-2 in eight municipalities of the Colombian tropics: high immunity, clinical and sociodemographic outcomes. (29th June 2021) - Garay, Evelin; Serrano-Coll, Héctor; Rivero, Ricardo; Gastelbondo, Bertha; Faccini-Martínez, Álvaro; Berrocal, José; Pérez, Alejandra; Badillo, María; Martínez-Bravo, Caty; Botero, Yesica; Arrieta, Germán; Calderón, Alfonso; et al.
Abstract: Background: Serological evaluation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an alternative that allows us to determine the prevalence and dynamics of this infection in populations. The goal of this study was to determine the clinical and sociodemographic dynamics of SARS-CoV-2 infection in a region of the Colombian Caribbean. Methods: Between July and November 2020, a cross-sectional observational study was carried out in Córdoba, located in northeast Colombia in the Caribbean area. Eight municipalities with the largest populations were chosen and 2564 blood samples were taken. A commercial enzyme-linked immunosorbent assay was used with the recombinant protein antigen N of SARS-CoV-2. The people included in the study were asked for sociodemographic and clinical data, which were analysed by statistical methods. Results: A seroprevalence of 40.8% was obtained for SARS-CoV-2 in the Córdoba region. In the bivariate analysis, no differences were observed in seropositivity against SARS-CoV-2 for gender or age range (p>0.05). Higher seropositivity was found in low socio-economic status and symptomatic patients (p<0.0001). A total of 30.7% of the asymptomatic patients were seropositive for SARS-CoV-2, which could be linked to the spread of this infection. In the multivariate analysis, seroconversion was related to poverty and clinical manifestations such as anosmia and ageusia (p<0.05). Conclusions: The high seropositivity in Córdoba is due to widespread SARS-CoV-2 in this population. The relationship between seropositivity and socio-economic status suggests a higher exposure risk to the virus caused by informal economic activities in low-income groups. Clinical manifestations such as anosmia and ageusia could be clinical predictors of infection by the new emergent coronavirus.